PERANCANGAN GAME “TALES OF SARIP TAMBAK OSO” BERBASIS DESKTOP MENGGUNAKAN UNITY - Alvito Dian Pratama Putra; Cindy Taurusta; Irwan Alnarus Kautsar (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Folklore is a story from the past that has been passed down from generation to generation in a society that serves as a medium to convey the values contained in the life believed by the community. One of the folktales originating from Sidoarjo that contains character education values in the development of the storyline is "Sarip Tambak Oso". However, in modern times and rapid technological developments like today, the folktale "Sarip Tambak Oso" and other folktales are at risk of extinction, because the impact of globalization has an impact on people's preferences, causing folklore to often be marginalized by popular cultural content from various countries. Therefore, it is necessary to design a game with a combined visual novel genre with an action genre entitled "Tales of Sarip Tambak Oso" as an effort to bring back the folklore of "Sarip Tambak Oso". The development of the Folklore Game "Tales of Sarip Tambak Oso" uses the GDLC (Game Development Life Cycle) method. Some tests that have been carried out are Black Box testing with 100% results and user response testing gets an average result of 89.5%, from the results of these percentages can be stated in the category of very good and is expected to be able to arouse public interest in the folklore of Sidoarjo which began to fade by the entry of outside culture.